Failure analysis on woven glass/epoxy composite laminates due to the effect of V-Notch and angle of fiber orientation / Mohamad Mali ... [et al.] - Mali, Mohamad; Hussain, Ahmad Kamil; Zahrullaili, Muhammad Ziyad; Alias, Muhammad Faliq; Mahmud, Jamaluddin (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Although the use of V-notch can significantly reduce the load-bearing capacity of structures, it is still widely used in engineering components due to some necessary design requirements. Despite the vast studies conducted on the effects of V-notch to composite structures, there is still a lack of studies related to the effects of the V-notch and angle variation of fiber orientation of composite laminates. Therefore, this study aims to investigate the effects of the V-notch and the variation of fiber orientation angle to the strength of Glass/Epoxy composite laminates through the failure behaviour of Glass/Epoxy composite laminates plain plate and V-notch plate under bending load. The study was conducted in two stages which comprised of numerical validation and failure analysis. For the failure analysis, a plane plate and V-notch under bending load were modelled by using ANSYS. Maximum Stress failure criterion were selected for failure prediction. The laminates were made of 24 layers woven Glass/Epoxy and the stacking sequence was (θ4/04/-θ4)s. The angle of fiber orientation, θ, was varied from 0° to 90° and failure loads for both plane plate and V-notch were determined. The trend of displacement and failure behaviour for plane plate and V-notch were compared to each other. From the results, it is found that the failure behaviour of V-notch is minimal from plane plate and was not affected by the variation of fiber orientation. This analysis and finding are important in aiding the engineers in designing a reliable V-notch on composite laminate. Therefore, it can be concluded that the current study is useful in contributing significant knowledge to better understand the failure behaviour of composite plate.